Issues of hope and faith in the cancer patient - Carni, Ellen (Journal of religion and health, 1988)
Akira Kurosawa's 1952 film about a man with a terminal gastric cancer introduces a discussion of hope and faith in the oncology patient. A psychodynamic relationship between hope and faith is explored, using Lawrence LeShan's research in cancer psychotherapy and Erik Erikson's lifespan developmental theory. LeShan describes a cancer personality characterized by hopeless despair, while Erikson formulates a psychogenetic framework for the development of hope and despair. Hope and faith are linked through the individual's earliest strivings toward basic trust in the world and his or her own self-efficacy. Accordingly, cancer psychotherapy may aim at restoring adult patients' faith in life and inner creative resources.